EDUCATIONAL MANAGEMENT IN AN ERA OF ARTIFICIAL INTELLIGENCE AND MACHINE LEARNING (Scientific Journal of Educational Management, Research and law, 2025)
The study used a descriptive survey research design to examine educational management in an era of artificial intelligence, AI, and machine learning, ML. The area of the study was the University of Nigeria Nsukka. The population consisted of 272 principal officers and other staff in management positions. A census sampling technique was employed for the study. The instrument for data collection was a researcher-structured questionnaire titled Questionnaire on Educational Management in the Era of Artificial Intelligence and Machine Learning (QOEMEAM). The validity of the instrument was tested using content analysis. Reliability was tested using the Pearson correlation coefficient (r). It gave a reliability coefficient of r = 0.810. SPSS statistical tool was employed for analysis. Research questions were answered using mean scores and standard deviation. Findings revealed that AI and ML enhance effective and efficient educational management (SD=1.2588 ˂ 1.402; (x ) ̅= 3.84 ˃ 3.0); AI and ML threaten the position of educational managers in educational management (SD=1.2588 ˂ 1.402; (x ) ̅=3.84 ˃ 3.0). It further revealed that educational managers should integrate AI and ML into educational management (SD=1.2588 ˂ 1.402; (x ) ̅=3.84 ˃ 3.0). The finding implies that the integration of AI and ML is important at this time but the implementation may lead to job loss by education managers. It was recommended that AI and ML be integrated into educational management but in phases, to the extent that it will not take over human roles and create job loss.